Caspase‐11: The driving factor for noncanonical inflammasomes. Issue 9 (5th September 2013) - Viganò, Elena; Mortellaro, Alessandra
<x xml:space="preserve">Abstract</x> Inflammasomes are large multiprotein platforms that mediate the processing of caspase‐1, which in turn promotes the maturation and release of IL‐1β and IL‐18 in response to microbial and danger signals. While the canonical pathway of inflammasome activation has been known for some time, a novel mechanism of noncanonical inflammasome activation mediated by caspase‐11 was more recently identified. This pathway engages caspase‐11 to trigger both caspase‐1‐dependent and ‐independent production of the inflammatory cytokines IL‐1β, IL‐18, and IL‐1α, as well as to promote pyroptosis, a form of genetically programmed cell death that is associated with the release of such cytokines. In this review, we gather together studies on both the mechanisms and implications of caspase‐11‐mediated noncanonical inflammasome activation, and discuss the emerging importance of this pathway in regulating host defense against intracellular bacterial pathogens.